TYPOLOGY AND SINGLE GRAIN U/PB AGES OF DETRITAL ZIRCONS FROM PROTEROZOIC SANDSTONES IN THE SW URALS (RUSSIA): EARLY TIME MARKS AT THE EASTERN MARGIN OF BALTICA - Willner A.P.; Sindern S.; Metzger R.; Ermolaeva T.; Kramm U.; Puchkov V.; Kronz A. (My University, 2003)
In the SW Urals a change of tectonic conditions occurred at around 620 Ma leading to a detrital input from contrasting provenance areas. Fifty-seven detrital zircons were separated from Proterozoic sandstones of this setting to study their typologies and pattern of U–Pb systematics.Detritus from Riphean sandstones (1.63–0.65 Ga) contains three populations of zircon: (1) completely rounded fragmental grains with complicated, but weak internal fabrics derived from high grade metamorphic areas with multistage reworking; (2) long-prismatic zircon grains with rounded edges and weakly preserved growth zoning from S-type granites; (3) types 1 and 2, but cloudy due to intense alteration (hydration of metamict areas). Zircons from Upper Vendian sandstones (0.62–0.54 Ga) comprise two groups: (1) zircons similar to those of Riphean populations 1, 2 and 3; (2) perfectly euhedral zircons with preserved magmatic growth zoning from potassic alkaline as well as acid magmas.Age signatures of polycyclic zircons from both Riphean and Upper Vendian detritus are compatible with crystallization in the interval of 1.8–2.3 Ga. This appears to be the significant age signature for the largely covered basement of the East European Platform, the presumed source region in the W. The pattern of U–Pb systems shows evidence of at least two events leading to lead loss. Data clusters in the concordia diagram confined to single samples show a remarkably strong influence of local sources. Alteration during diagenesis was an important factor of lead loss.Upper Vendian detrital zircons have two sources: (1) The majority of the polycyclic rounded zircons also has a Paleoproterozoic crystallization age consistent with that of the Riphean detrital zircons. However, a few zircon grains point to a later anorogenic event which does not match with known events in the Riphean basin and hence underline an allochthonous character of the source area. (2) The data of the euhedral zircon would reflect a source age between 643 and 512 Ma.The latter age signature is compatible with a local magmatic event concomitant with exhumation and emplacement of the allochthonous Beloretzk Terrane after 620 Ma. This eastern source area for the Upper Vendian detritus had partly been affected by high-pressure/low temperature metamorphism. The change of tectonic conditions reflected by the detritus composition represents a change from a passive continental margin along the Rodinia supercontinent persisting during the Riphean to a convergent continental margin during the Upper Vendian within a transpressional setting.
Keywords: Zircon typology; Detrital zircon; Single grain U/Pb systematics; Timanide orogeny; Riphean sandstone; Vendian sandstone; Rodinia; SW-Urals; Precambrian::Proterozoic::Riphean; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский; Докембрий::Протерозой::Рифей